School Journalism Training for Nurturing Young Creative and Critical Journalists - Ahmad Salman Farid; Muhammad Ardiansyah (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
This article explores the importance of a School Journalism Training program aimed at nurturing young creative and critical journalists. In an era where media plays a pivotal role in shaping public opinion, it is essential to equip the younger generation with the skills needed to analyze, report, and create content with integrity and critical thought. This training focuses on developing creativity, critical thinking, and ethical journalism practices among students. By engaging in practical exercises and collaborative projects, participants will learn the core principles of journalism, including research, writing, editing, and multimedia production. The training encourages students to approach stories from diverse perspectives, fostering a sense of responsibility and social awareness. The objective is not only to enhance their journalistic skills but also to cultivate a new generation of journalists who are both innovative and thoughtful in their work. This initiative ultimately contributes to the growth of an informed society, prepared to face the challenges of an ever-evolving media landscape.